The role of renewable energy in achieving water, energy, and food security under climate change constraints in South Asia - Neupane, Nilhari; Chaudhary, Pashupati; Rijal, Yashoda; Ghimire, Bishal; Bhandari, Roshan (Frontiers in Sustainable Food Systems, 2022)
The energy demand in South Asia is increasing at a rapid rate and it is becoming harder to meet the demand due to the high cost of conventional energy sources, the unsustainability of energy use, and the high emissions caused by the energies. South Asia is blessed with a high potential for renewable energy, especially hydropower, but that has not been adequately tapped. This has highly compromised the food, water, and energy security of the people in South Asian countries. This article identifies the roles of renewable energy sources in achieving energy, water, and food security for South Asian nations and provides suggestions for enhancing the utilization of renewable resources. The article identifies the potential for the promotion of hydropower and other renewable energy sources as well as opportunities and potential challenges for multilateral energy trade for increasing the availability of energy. It also recommends possible solutions and approaches for the promotion of hydropower and other renewables in South Asia. The article infers that a nexus approach for integrated planning, policy coherence, and institutional harmonization increases the benefit by reducing transaction costs, generating additional synergies, and reducing the trade-off at different scales. These approaches enhance energy, food, and water security, and eventually improve the quality of life in the region. Improved access to renewable energy can contribute directly and indirectly to achieving Sustainable Development Goals (SDGs) in this region.